2019
DOI: 10.1029/2019gl083201
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Network Imaging on Rock Slope Instabilities Using Resonance Mode Analysis

Abstract: We performed modal analysis using frequency domain decomposition of ambient seismic vibration data collected on large rock slope instabilities. This technique enables a robust detection of resonance frequencies and provides the corresponding mode shape vectors. We applied the technique to synthetic and field data sets acquired by seismometer arrays on two rock instabilities in Switzerland. We found that, at the fundamental mode, the entire instability vibrates in‐phase with the dominant mode shape vector orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 35 publications
5
35
2
Order By: Relevance
“…Compared to the findings by Häusler et al (2019), who identified f2 at 4.7 Hz in a dataset acquired using a similar temporary seismic array in 2012, the mode shapes are not perfectly repeatable. Note that the area of the southeastern high amplification area was not covered in the array by Häusler et al (2019). Even if only those locations are considered which were previously surveyed in 2012, the resonance frequency f2 is much more pronounced in the data acquired in 2019 than in the data of 2012 (comparison in Figure S4).…”
Section: Results Of Array-based Fdd Modal Analysis Using Ambient Vibrcontrasting
confidence: 93%
See 3 more Smart Citations
“…Compared to the findings by Häusler et al (2019), who identified f2 at 4.7 Hz in a dataset acquired using a similar temporary seismic array in 2012, the mode shapes are not perfectly repeatable. Note that the area of the southeastern high amplification area was not covered in the array by Häusler et al (2019). Even if only those locations are considered which were previously surveyed in 2012, the resonance frequency f2 is much more pronounced in the data acquired in 2019 than in the data of 2012 (comparison in Figure S4).…”
Section: Results Of Array-based Fdd Modal Analysis Using Ambient Vibrcontrasting
confidence: 93%
“…Burjánek et al (2018) also observed strong polarization phenomena perpendicular to the failure scarp and the open fractures. This normal mode behavior was later reassessed by Häusler et al (2019) using frequency domain decomposition (FDD) modal analysis. This study also analyzed higher modes and concluded that the observed mode shapes and amplification factors can only be explained by an additional rear fracture potentially limiting the extend of the entire rock instability (dashed line in Figure 2).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike blasting vibration velocities that are easily influenced by external conditions, natural frequencies of rock masses are intrinsic characteristics and relatively simple to obtain without knowing near-field vibration data. Based on commonly recorded blasting vibration data, natural frequencies of rock masses can be extracted by diverse methods, such as Fourier spectra [ 37 , 38 ], the power spectral density (PSD) [ 39 , 40 ], the transfer function [ 41 , 42 ], the frequency domain decomposition method [ 43 , 44 ], spectral ratios [ 45 , 46 ], and polarization analysis [ 40 , 47 ]. Researchers have developed a number of techniques to identify the location and degree of damage in structures using the change in the natural frequency in structural health monitoring [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%